Polo-like kinase 1 is related with malignant characteristics and inhibits macrophages infiltration in glioma - Luo, Lin; Zhang, Xiao-Yang; Zhen, Ying-Wei; Guo, Gao-Chao; Peng, Da-Zhao; Wei, Cheng; Pei, Dong-Ling; Yu, Bin; Ji, Yu-Chen; Liu, Xian-Zhi; Han, Lei; Zhang, Zhen-Yu (Frontiers in Immunology, 2022)
Background: Tumor immune microenvironment (TIM) plays a critical role in tumorigenesis and progression. Recently, therapies based on modulating TIM have made great breakthroughs in cancer treatment. Polo-like kinase 1 (PLK1) is a crucial regulatory factor of the cell cycle process and its dysregulations often cause various pathological processes including tumorigenesis. However, the detailed mechanisms surrounding the regulation of PLK1 on glioma immune microenvironment remain undefined. Methods: Public databases and online datasets were used to extract data of PLK1 expression, clinical features, genetic alterations, and biological functions. The EdU, flow cytometry, and macrophage infiltration assays as well as xenograft animal experiments were performed to determine the relationship between PLK1 and glioma immune microenvironment in vivo and in vitro. Results: PLK1 is always highly expressed in multiple cancers especially in glioma. Univariable and Multivariate proportional hazard Cox analysis showed that PLK1 was a prognostic biomarker for glioma. Simultaneously, highly expressed PLK1 is significantly related to prognosis, histological and genetic features in glioma by analyzing public databases. In addition, the enrichment analysis suggested that PLK1 might related to “immune response”, “cell cycle”, “DNA replication”, and “mismatch repair” in glioma. Immune infiltration analysis demonstrated that highly expressed PLK1 inhibited M1 macrophages infiltration to glioblastoma immune microenvironment by Quantiseq and Xcell databases and negatively related to some chemokines and marker genes of M1 macrophages in glioblastoma. Subsequent experiments confirmed that PLK1 knockdown inhibited the proliferation of glioma cells but increased the M1 macrophages infiltration and polarization. Furthermore, in glioma xenograft mouse models, we showed that inhibiting PLK1 blocked tumor proliferation and increased the M1 macrophages infiltration. Finally, PLK1 methylation analysis and lncRNA-miRNA network revealed the potential mechanism of abnormal PLK1 expression in glioma. Conclusions: PLK1 inhibits M1 macrophages infiltration into glioma immune microenvironment and is a potential biomarker for glioma.